Inner Consciousness Tindakan Nabi - Umam, Muchammad Helmi (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2011)
The article is written to examine deeds and actions of the Prophet Muhammad (peace be upon him) within inner consciousness analysis of Husserl?s phenomenology. The article is formulated to explore the significance of phenomenology of religious study, Prophet?s deeds as well as his inner consciousness, and inner consciousness analysis of Prophet?s deeds. This article is written using phenomenological method, i.e. a comprehensive interpretation about the source of information or object?s phenomenon as long as it can be traced. Inner consciousness of Prophet?s actions sees that his deeds in deciding important religious pronouncements were results of long-term memory based on divine and social argumentations, which have came into Prophet?s consciousness as a human.